In-Vitro Growth of Transgenic Sengon Resulting From Co-Cultivation Using Agrobacterium Tumefaciens Bacteria - Aslan, Aura Aulia; Larekeng, Siti Halimah; Rachmat, Agus; Restu, Muhammad (ITScience (Information Technology and Science), 2024)
Sengon (Paraserianthes falcataria (L) Nielsen) is a forestry plant often developed for industrial purposes in Indonesia. Sengon is a fast-growing species and has a relatively short-cutting period. Sengon wood is widely used in the production of carpentry wood, plywood raw materials, and pulp. The purpose of this study was to optimize the transformation of the entC and pmsB genes into sengon plants using the embryo injury method through Agrobacterium tumefaciens as an intermediary and to determine the efficiency of the transformation using the injury to sengon embryos. This research was conducted from September 2022 to March 2023. The research was conducted at the Genetically Modified Organism (GMO) Tissue Culture Laboratory, Recombinant Protein (Microbe) Laboratory, and Greenhouse of the Genetic Engineering Center, National Research and Innovation Agency (BRIN) Cibinong, Bogor, Java West. The research procedure consisted of several steps, namely Preparation of MS Media, Preparation of LB Media, Preparation of Sengon Seed Infection Using Agrobacterium tumefaciens, Sterilization and Planting of Sengon Seeds, Acclimatization, and Molecular Analysis (including Sengon DNA isolation, PCR Amplification, and Electrophoresis). Transformation efficiency was calculated by the positive strain of hpt PCR bands compared to the number of transformed embryos and multiplied by 100%. In the results of the PCR analysis, it was found that one plant sample carried the hpt marker, which indicates the integration of the entC and pmsB genes. which when analyzed using transformation efficiency calculations, the data obtained for the entire transformation stage was 0.8%, where the success of the transformation obtained was still classified as low. Factors that cause the low success of transformation include the method of transformation, the growth phase of bacteria, genetic material, and culture aseptic conditions.